Physical therapist role in schools: An experience according the students perspective (2013)
Background. Since 2004, there have been references to the educational field as a scenario in the practice of physical therapy. The Department of Human Body Movement (DHBM), accepting this proposal, developed a professional practice in this area with an approach from the categories body, corporeality and human body movement. Objective. To identify the appreciation of physical therapy students in regards to the association of body and corporeality categories to the educational area; to design and implement coordinated actions relevant to the needs and characteristics of the population; to contribute from the experience to the professional practice as physical therapist; scope and limitations of the strategies implemented. Materials and methods. This is a descriptive qualitative study. The information was obtained from written records that physical therapy students did. The author conducted additional semi-structured interviews and focus groups discussions with them. Results. There is necessary a greater contextualization in regards to concepts of body, corporeality and movement to ensure that all students achieve insertion into practice. The methodology used allowed the use of strategies that were coherent with the needs and characteristics of the population. Mostly all participants displayed this practice setting as a future professional area but manifested difficulties in developing the activities and achievements of the same. Conclusion. The physical therapist specialist and the schools need specific actions to promote participation and teacher empowerment regarding the design and implementation of projects in the educational scenario. It is required to research other stakeholders perception involved in the experience.